Analysis of the Impact of Macroeconomic Inflation on the Profitability Performance of PT Vale Indonesia Tbk: An Empirical Regression Approach for the 2018-2023 Period - Fakhirah Husain; Nurul Mutmainnah; Andre Rachmansyah Putra Tira; Fera Anastasya; Putri Nur Ramadhani (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to examine and analyze the influence of macroeconomic inflation on the profitability performance of PT Vale Indonesia Tbk during the 2018–2023 period. Profitability is a key indicator of a company’s financial health, and understanding how it responds to macroeconomic fluctuations is essential, particularly in the mining industry, which is highly sensitive to global and domestic economic conditions. This research employs a quantitative approach using simple linear regression analysis, supported by secondary data consisting of company financial statements and annual inflation data retrieved from the Central Statistics Agency (BPS) and Bank Indonesia. Several classical assumption tests were conducted, including normality, autocorrelation, and multicollinearity tests. The results show that the data are normally distributed and free from multicollinearity; however, the model exhibits positive autocorrelation, indicating that the residuals are not fully independent across time. The regression analysis reveals that inflation has a negative influence on the company’s profitability, measured by Return on Assets (ROA). Nevertheless, this relationship is not statistically significant, as reflected by a significance value of 0.677 (> 0.05). Furthermore, the coefficient of determination (R²) of 0.066 and an adjusted R² of -0.245 indicate that inflation explains only 6.6% of the variation in ROA, while the remaining 93.4% is influenced by other internal and external variables not included in this model. Overall, the findings suggest that inflation does not have a significant impact on the profitability of PT Vale Indonesia Tbk during the study period, implying that the company’s financial performance may be more strongly affected by operational efficiency, commodity prices, production volume, and other macroeconomic indicators beyond inflation.